The Effect of Mergers and Acquisitions on Bank Performance in Ghana - Musah, Alhassan; Abdulai, Mohammed; Baffour, Hilda (Asian Journal of Economics and Empirical Research, 2020)
The study examined the consequence of mergers and acquisition on bank performance in Ghana. Specifically, the study investigated the effect of mergers and acquisition on net profit margin, return on assets and return on equity of commercial banks in Ghana. Data from the annual reports of eight (8) commercial banks over a 10-year period (2009-2018) were collected and analysed by the use of descriptive statistics, correlation analysis, and regression analysis. The findings revealed a negative and significant association between mergers and acquisition and net profit margin. There existed a positive but statistically insignificant relationship between mergers and acquisition and return on assets of commercial banks in Ghana. Further, there was a negative but statistically insignificant relationship between mergers and acquisition and return on equity. The results, however, could not establish a conclusive evidence of the impact of mergers and acquisition on bank performance, implying that mergers and acquisition might not necessarily improve bank financial performance.